Dampak Direct Selling Online terhadap Pedagang Pasar Tradisional: Perspektif Ekonomi Syariah - Rasyidah Bulqis (Mappideceng:Jurnal Ekonomi Syariah, 2024)
The rapid growth of e-commerce and online direct selling has changed the trade landscape significantly. This phenomenon has complex impacts, especially for traditional market traders who have existed for centuries. This research aims to analyze in depth the impact of online direct sales on traditional market traders, taking into account the sharia economic perspective. The impact of online direct selling on traditional market traders is complex and multidimensional. The emergence of online direct selling has created increasingly fierce competition for traditional market traders. Ease of access, various product choices, and competitive price offers are the main attraction for consumers. Challenges and opportunities exist simultaneously. With the right government policies and joint efforts from all parties, it is hoped that a harmonious balance can be created between the development of online business and the business continuity of traditional market traders.